A Numerical Simulation of Convection and Conduction Heat Transfer for a Fluid in a Porous Medium (European Journal of Pure and Applied Mathematics, 2023)
Building a computational formula which is expressed by a system of nonlinear partial differential equations in two components was done in this job. The matter of energy transfer by free convection of a dissipative liquid running in a horizontal channel with a porous medium was examined in this study, and we describe the behavior of fluid flow through the channel and the temperature distribution within it. Numerical methods were used as the ODE45 method, one of the Rang-Kutta methods for processing the resulting differential equations. The effect of the Prandtl number, the Schmidt multitude, and the Gratshof amount were also studied.
Keywords: Heat Transfer, Prandtl number, Schmidt number, Gratshof number, ODE45 Method.